Effectiveness of device-guided breathing in chronic coronary syndrome: a randomized controlled study - YILDIZ ÖZER, AYSEL (My University, 2023)
Background: Chronic coronary syndrome (CCS) is one of the most life-restricting coronary artery diseases, and symptom relief is the main goal in CCS patients who suffer from angina. Objectives: To assess the potential benefits of device-guided breathing in CCS patients with angina in this randomized, controlled, single-blinded study. Methods: Fifty-one patients with CCS received device-guided breathing for 7 days/8 weeks. Exercise capacity [exercise stress test], cardiac function [transthoracic echocardiography], and angina severity [Canadian Cardiovascular Society Classification] were evaluated initially and after the training. Device-guided breathing was performed at the lowest resistance of the device (POWERbreathe Classic LR) for the control group (n = 17). The low load training group (LLTG; n = 18) and high load training group (HLTG; n = 16) were trained at 30% and 50% of maximal inspiratory pressure. Baseline characteristics were compared using one-way ANOVA and Kruskal-Wallis test. Categorical data were compared using the chi-square test. ANCOVA was performed to compare changes between three groups. A p value < 0.05 was considered statistically significant. Results: Metabolic equivalent values were significantly improved in both HLTG and LLTG groups (p < 0.001, p = 0.003). The Duke treadmill score significantly improved and shifted to low-risk both in the HLTG (p < 0.001) and LLTG (p < 0.001) groups. Angina severity significantly alleviated after the training in both HLTG and LLTG groups (p < 0.001, p = 0.002). Conclusions: An 8-week long program of short-term respiratory muscle training provided positive gains in exercise capacity and angina severity in CCS patients with angina. The effects of long-term training programs on CCS patients should be investigated clinically because of the possibility of helping to decrease the need for invasive treatments.
Keywords: Atherosclerosis; Chronic stable angina; Exercise test; Respiratory muscle training